ANÁLISE LABORATORIAL DE PROPRIEDADES ÓPTICAS E TÉRMICAS DE DEZESSEIS AMOSTRAS DE TELHAS DISPONÍVEIS NO MERCADO BRASILEIRO - Krelling, Amanda Fraga; Silva, Milena Paim da; Souza, Rodrigo Vargas; Marinoski, Deivis Luis; Güths, Saulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Roofs commonly represent the surface on which solar radiation is most strongly incident, evidencing a necessity to study thermal performance. In this paper, emittance and reflectance of sixteen roof tile samples commercialized in the Brazilian market have been measured and analyzed, with evaluation focused on a hot climate context. The selected samples were separated according to seven different categories: Shingle, ceramics, fiber cement, metallic, concrete, vegetal fiber and Tetra Pak. The method of emittance measurement was based on the American Society for Testing and Materials (ASTM) C1371-10 Standard, while reflectance evaluation was based on ASTM Standards E903 and C1549. Results were applied to the Solar Reflectance Index (SRI) calculation, adopted by the Leadership in Energy and Environmental Design (LEED) certification urban heat island mitigation potential. The lowest SRI values were obtained for Shingle tiles (ranging from -2 to 25), regardless of their color, followed by the vegetal fiber tile. On the other hand, white colored ceramic and fiber cement tiles presented high SRI indexes (97 and 91, respectively). Results obtained here may serve as reference for buildings performance evaluations, such as the Brazilian Standard NBR 15.757 and the Quality Technical Regulation (RTQ).